Endogamy and Marriage Customs in Kashubia and the Question of the So-Called Kashubian Gene - Kwaśniewska, Anna (Studia Etnologiczne i Antropologiczne, 2019)
One of the genetic disorders is LCHAD deficiency. It occurs relatively often in Kashubian population, which is among others attributed to endogamy. Before the second half of the 20th century the Kashubs majorly married within a single parish or a town, village. Also in this day and age, in Kashubia people most of all wed someone living in the neighbouring area. It stems from powerful family and group (ethnic) ties, the traditional family model, low level of education. The Kashubs’ close adherence to family values is best expressed in robust wedding ceremonies along with commonly celebrated Polterabend. This social gathering exhibiting some analogies with potlatch, serves as a kind of status marker for a particular family’s popularity; it confers prestige and indicates position within local community. Despite some anxiety brought about by the promulgation of knowledge about “Kashubian gene,” there is no visible tendency in Kashubian community to change the model of spouse selection.